Role of intrinsic factors in impulsive buying decision: An empirical study of young consumers - Shakeel Ahmad Sofi; Fayaz Ahmad Nika (Arab Economic and Business Journal, 2017)
The primary aim of the current research was to study the effect of various intrinsic factors on consumer decision making vis-à-vis [41TDDIF]impulsive buying tendencies. After employing EFA and CFA on 630 consumers in the different parts of Jammu and Kashmir, results showed that intrinsic factors significantly influence the Impulsive Buying Decision. The application of Structural Equation Modeling disintegrated intrinsic factors into positive and negative influencers of [62TDDIF]impulsive buying behaviour. The present study has significant bearing in consumer world as it has highlighted through a model for how intrinsic factors shape the buying tendencies of a young consumer. Through the application of Multi Group Analysis, a comparison has been drawn between impulsive buying behaviour and various intrinsic factors across males and females taken as two different consumer groups. Overall results have been found significant and could well be adopted for strategy making by various stake holders in the field of consumer psychology and consumer behaviour to figure out the effects of intrinsic factors on buying behaviour.
Keywords: 650; Impulsive buying behaviour; Intrinsic factors; Gender differences; Multi group analysis